The water elemental / Muhammad Irfan Mohamad Anuar ... [et al.] - Mohamad Anuar, Muhammad Irfan; Shahrul Azri, Nur Aisyah; Roszamri, Hajar (2024)
The concept and benefits of creating an open space pavilion for students at a university campus revolve around enhancing the student experience. The pavilion serves as a multifunctional outdoor area designed to enhance the student experience. It provides a welcoming environment for relaxation, and socialization among students. The pavilion aims to create a harmonious connection between students and nature while providing a versatile and functional environment for various activities.